2013
DOI: 10.1016/j.febslet.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Rim15‐dependent activation of Hsf1 and Msn2/4 transcription factors by direct phosphorylation in Saccharomyces cerevisiae

Abstract: Edited by Berend WieringaKeywords: Hsf1 Msn2/4 Phosphorylation PKA Rim15 a b s t r a c t Rim15 kinase, a downstream effector of PKA and TORC1 signaling pathways, initiates the quiescent program upon nutrient starvation via induction of genes whose expression depends on transcription factors Msn2, Msn4, and Gis1. Here, we demonstrate that Rim15 also induces expression of Hsf1 target genes upon glucose depletion by both transcriptional activation and stabilization of the transcripts. Rim15 phosphorylates Hsf1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 22 publications
3
72
0
Order By: Relevance
“…Multiple phosphorylation sites have been mapped on Hsf1 (Anckar and Sistonen, 2011; Guettouche et al, 2005), and mutational analysis has suggested activating, repressing, fine-tuning and condition-specific roles for individual sites of phosphorylation in yeast and mammalian cells (Budzynski et al, 2015; Cho et al, 2014; Dai et al, 2015; Hahn and Thiele, 2004; Hashikawa et al, 2006; Hashikawa and Sakurai, 2004; Hietakangas et al, 2003; Høj and Jakobsen, 1994; Holmberg et al, 2001; Kline and Morimoto, 1997; Knauf et al, 1996; Lee et al, 2013; Soncin et al, 2003; Sorger and Pelham, 1988; Tang et al, 2015; Wang et al, 2003; Yamamoto et al, 2007). Recent work in which 15 phosphorylation sites were simultaneously mutated in human Hsf1 failed to disrupt Hsf1 activation during heat shock (Budzynski et al, 2015), and a genome-wide RNAi-based screen for modulators of Hsf1 activity found no evidence for kinase regulation (Raychaudhuri et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple phosphorylation sites have been mapped on Hsf1 (Anckar and Sistonen, 2011; Guettouche et al, 2005), and mutational analysis has suggested activating, repressing, fine-tuning and condition-specific roles for individual sites of phosphorylation in yeast and mammalian cells (Budzynski et al, 2015; Cho et al, 2014; Dai et al, 2015; Hahn and Thiele, 2004; Hashikawa et al, 2006; Hashikawa and Sakurai, 2004; Hietakangas et al, 2003; Høj and Jakobsen, 1994; Holmberg et al, 2001; Kline and Morimoto, 1997; Knauf et al, 1996; Lee et al, 2013; Soncin et al, 2003; Sorger and Pelham, 1988; Tang et al, 2015; Wang et al, 2003; Yamamoto et al, 2007). Recent work in which 15 phosphorylation sites were simultaneously mutated in human Hsf1 failed to disrupt Hsf1 activation during heat shock (Budzynski et al, 2015), and a genome-wide RNAi-based screen for modulators of Hsf1 activity found no evidence for kinase regulation (Raychaudhuri et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…RIM15 encodes a conserved Greatwall-like protein kinase involved in the control of mitotic cell cycle progression (9). The role of Rim15p in initiating the G 0 program has been well established, particularly in yeast (10,11), and more recently, Rim15p was shown to directly phosphorylate and thereby enhance the activities of Msn2/4p and Hsf1p associated with G 0 entry (12). In addition, deletion of the RIM15 gene markedly reduces stress tolerance and accelerates alcoholic fermentation by both laboratory and industrial yeast strains (8,13).…”
mentioning
confidence: 99%
“…Rim15 is required for the metabolic changes that accompany quiescence 207 and also activates the endosulfine, Igo1, which helps maintain mRNA populations during quiescence 208209210. Rim15 also activates the Msn2/Msn4 transcription factors, which directly activate stress response genes necessary for quiescence 86211, and Rim15 is also required for the lifespan extension caused by calorie restriction 115212. In addition to its role in quiescence, Rim15 is required for both the expression and activity of Ime1 213214215.…”
Section: Varying Fates Varying Functionsmentioning
confidence: 99%